Risk factors responsible for atrial fibrillation development between symptomatic patients with concealed or manifest atrioventricular accessory pathways. (1st June 2015) - Chen, Mu; Feng, Xiangfei; Sun, Jian; Wang, Qunshan; Zhang, Pengpai; Wang, Jun; Li, Yi-Gang
Abstract: Background: Patients with manifest atrioventricular accessory pathways (mAPs) have a greater tendency to develop atrial fibrillation (AF) compared with patients with concealed atrioventricular accessory pathways (cAPs). However, the risk factors of developing AF in patients with various atrioventricular accessory pathways (APs) are not clear. Methods: This retrospective study included 460 symptomatic patients with either cAPs (n = 246) or mAPs (n = 214) who underwent electrophysiological study and successful radiofrequency catheter ablation of APs. Clinical and electrophysiological characteristics were compared between cAPs and mAPs and between AF and non-AF groups with cAPs or mAPs. Independent risk factors of AF were analyzed using multivariate logistic regression. Results: AF was more frequent in mAPs group than in cAPs group (23.4% vs 9.8%, p < 0.01). Clinical features were similar between cAPs and mAPs. Anterograde conduction properties served as the major electrophysiological feature of mAPs. Multivariate analysis indicated that mAPs, hypertension, post-ablation P wave dispersion (Pd), N-terminal proB-type natriuretic peptide (NT-proBNP) and creatinine were independent risk factors of AF in the complete cohort. Hypertension, post-ablation Pd and high-sensitivity C-reactive protein (hsCRP) were independent risk factors of AF in cAPs group. Post-ablation Pd, NT-proBNP, creatinine and shorter effective refractory period of anterograde accessory pathways (AAP ERP) were independent risk factors of AF in mAPs group. Conclusions: Results from this study demonstrate that the risk factors of AF are not homogenous between concealed and manifest APs, which might suggest heterogeneous pathogenesis of AF in these two types of APs.